2011
DOI: 10.1103/physreva.84.013833
|View full text |Cite
|
Sign up to set email alerts
|

Scattering of linear and nonlinear waves in a waveguide array with aPT-symmetric defect

Abstract: We study the scattering of linear and nonlinear waves in a long waveguide array with a parity-time (PT)symmetric defect created by two waveguides with balanced gain and loss. We present exact solutions for the scattering of linear waves on such a defect, and then demonstrate numerically that the linear theory can describe, with a good accuracy, the soliton scattering in the case of weak nonlinearity. We reveal that the reflected and transmitted linear and nonlinear waves can be amplified substantially after in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 21 publications
0
54
0
Order By: Relevance
“…Recently in nonlinear optics a great deal of attention has been focused on the effect of soliton interaction with the complex PT-symmetric localized potentials embedded into the self-focusing or selfdefocusing medium. In these settings the PT-symmetric gain and loss regions are spatially localized, e.g, in the form of nonlinear PT-symmetric dimers, trimers, or, more generally, oligomers embedded into nonlinear conservative lattice [59,156,162,163]. Continuum versions of such models have been analyzed in the works [164][165][166].…”
Section: Soliton Scatteringmentioning
confidence: 99%
“…Recently in nonlinear optics a great deal of attention has been focused on the effect of soliton interaction with the complex PT-symmetric localized potentials embedded into the self-focusing or selfdefocusing medium. In these settings the PT-symmetric gain and loss regions are spatially localized, e.g, in the form of nonlinear PT-symmetric dimers, trimers, or, more generally, oligomers embedded into nonlinear conservative lattice [59,156,162,163]. Continuum versions of such models have been analyzed in the works [164][165][166].…”
Section: Soliton Scatteringmentioning
confidence: 99%
“…This is possible in conservative systems because the translational kinetic energy of the breather can be partly converted into its internal energy and vice versa. Scattering of linear and nonlinear waves (solitons) on defects in PT -symmetric optical waveguide arrays was analyzed [24,25,[29][30][31]. It was shown that the incident highamplitude solitons (or even linear wave packets [24,25]) can excite a mode localized on the PT -symmetric defect.…”
Section: Introductionmentioning
confidence: 99%
“…These include, among others, unconventional beam refraction [13], Bragg scattering [14], symmetry-breaking transitions [4] and associated ghost states [15][16][17][18], a loss-induced optical transparency [5], conical diffraction [19], a new type of Fano resonance [20], chaos [21], nonlocal boundary effects [22], optical switches [23] and diodes [24,25], phase sensitivity of light dynamics [26][27][28], and the possibility of linear and nonlinear wave amplification and filtering [29][30][31]. Unexpected instabilities were also * saadatmand.d@gmail.com † dmitriev.sergey.v@gmail.com ‡ borisovdi@yandex.ru § kevrekid@math.umass.edu identified at the level of PT -symmetric lattices, and nonlinear modes were identified in few-site oligomers, as well as in full lattice settings both in one dimension [32][33][34][35][36][37] and even in two dimensions [38].…”
Section: Introductionmentioning
confidence: 99%
“…The scattering of usual continuous and discrete solitons by localized PT potentials have been recently investigated in [12] for the case of Scarf II type PT potential, and in [13] for PT defects in quasi-linear regime where it has been shown that reflected and transmitted small amplitude waves can be amplified in the scattering process. The possibility of soliton switching in a PT-symmetric coupler induced by the gain and loss properties of the PT defect was also suggested in [14].…”
Section: Introductionmentioning
confidence: 99%